Kinetic Characteristics of Spermatozoa of Saanen Goats After Cryopreservation - Bogdaniuk, Anastasiia O.; Berestovyy, Oleh O.; Tsvik, Vasil V. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 169.